An Unusual Deformity of the Lateral Meniscus in a Dog - Robins, G. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
In the dog meniscal injuries are usually secondary to rupture of the cranial cruciate ligament. In man a discoid meniscus is a well recognised morphological anomaly of the knee (5). In contrast discoid meniscal lesions are rarely diagnosed in the dog (6). This paper presents the clinical findings in a dog with a bilateral ring-shaped lateral meniscal deformity and an abnormal location of the tendon of the m. popliteus.
Keywords: Ring-shaped meniscus; Cruciate rupture; Popliteal tendon displacement